KARAKTERISTIK HIDRODINAMIK DAN PERPINDAHAN KALOR PADA FENOMENA FLOODING DALAM PIPA PANAS VERTIKAL - , Mahmuddin, Ir.,MT., Ir. Samsul Kamal, MSc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Experiments have been conducted on countercurrent flow and water in a vertical pipe. These covered the characteristics of film flow and onset of flooding (OF) which were mapped against time and distance measurement and the influence of film thickness and the OF characteristics of heat transfer. The study was conducted in two stages, The first was the adiabatic process (Research 1) and the second was non-adiabatic processes (Research 2). Water flowed from the top side of the pipe through porous media prior entering the test section and the air was injected axially from the bottom side. Variations in water Reynolds numbers (ReL) was 322 to 2446 and air Reynolds number (ReG) was 4446 to 13941. Test section of adiabatic process is made of transparent flexiglass tube equipped with a sensor film thickness. The sensor consists of two parallel wires mounted at a distance (Z) of 400 mm, 1600 mm and 2200 mm below the water injector. The variation of the film thickness was measured with conductance method using two pin prallel type . Test Section of non-adiabatic process is a hot pipe from copper material. Test section is equipped with a temperature sensor film flow, temperature sensors surface pipe wall and the sensor film thickness. The sensors are mounted circumferally at 120 o each at the the distance of 1450 mm, 1600 mm and 1750 mm in front of water injector. The signal from each sensor will be acquired ith the LM324 component then digitized with a LabJack U12 PH OEM. Electrical circuit of the sensor is equipped with transducers that can change the input data of temperature and water resistance in the form of electrical voltage. The data measurement will be recorded simultaneously by means of data acquisition. Increased air velocity can cause the layer of film that is tangent to the flow of air pushed upward but, the film in near surface of the pipe wall was not affected. This phenomenon is konown as the onset of flooding. At low ReL OF initialized at the botton of the pipe and was indicated by a sudden increased of the film thickness. The sudden increase of film thickness is also known as hydraulic jump look like. The OF may decrease the wall temperature and inceease the heat transfer coeficient. In contrary, at high ReL Of started at the upperside of the pipe and was indicated by sudden decrease of the film thickness. Hence, the wall temperatures increased and the convestion heat transfer coefficient decreased simultaneously.